Early aseptic loosening of a mobile-bearing total knee replacement: A case-control study with retrieval analyses. (2nd January 2018) - Kutzner, Ines; Hallan, Geir; Høl, Paul Johan; Furnes, Ove; Gøthesen, Øystein; Figved, Wender; Ellison, Peter
Abstract : Background and purpose — Registry-based studies have reported an increased risk of aseptic tibial loosening for the cemented Low Contact Stress (LCS) total knee replacement compared with other cemented designs; however, the reasons for this have not been established. We made a retrieval analysis with the aim of identifying the failure mechanism. Patients and methods — We collected implants, cement, tissue, blood, and radiographs from 32 failed LCS Complete cases. Damage to the tibial baseplate and insert was assessed. Exposure to wear products was quantified in 11 cases through analysis of periprosthetic tissue and blood. Implant alignment and bone cement thickness was compared with a control group of 43 non-revised cases. Results — Loosening of the tibial baseplate was the reason for revision in 25 retrievals, occurring at the implant–cement interface in 16 cases. Polishing was observed on the lower surface of the baseplate and correlated to the level of cobalt, chromium, and zirconium in the blood. No evidence of abnormally high polyethylene wear was present. For each 1 mm increase in cement thickness the odds of failure due to aseptic loosening decreased by 61%. Greater varus alignment was associated with a shorter time to failure. The roughness, Ra, of a new LCS baseplate's lower surface was 3.7 (SD 0.7) µm. Interpretation — Debonding of the tibial component at the implant–cement interface was the predominant cause of tibial aseptic loosening. A thin cement layer may partly explain the poor performance. Furthermore, the comparatively low tibial surface roughness and the lack of a keeled stem may have played a role in the failures observed.